PROSES KOGNITIF PADA PENGHAFAL AL-QUR’AN - Diba, Icha Fara; Muhid, Abdul (STAI Tuanku Tambusai, 2022)
ABSTRACTMemorizing the Qur'an is an effort to remember, understand the content in the Qur'an and to maintain its authenticity. Studying the Qur'an is obligatory and memorizing the Qur'an is fardhu kifayah. However, the benefits of memorizing the Qur'an on human intelligence are enormous. In this article the focus aims to explain the cognitive process of memorizing the Qur'an in which it will be studied from psychological factors that affect the cognition of memorizing the Qur'an. Both from intelligence, emotional and spiritual intelligence. So the authors found the impact of the cognitive process of memorizing the Qur'an. This article uses a literature review research method. The findings of this study indicate that there are several ethics in memorizing the Qur'an in accordance with Islamic teachings, stages of the cognitive process in memorizing the Qur'an and psychological factors that affect memorizing the Qur'an.